2021
DOI: 10.3390/rs13234897
|View full text |Cite
|
Sign up to set email alerts
|

Down-Looking Airborne Radar Imaging Performance: The Multi-Line and Multi-Frequency

Abstract: The paper proposes an analytical study regarding airborne radar imaging performances and accounts for a down-looking radar system moving along parallel lines far, in terms of probing wavelength, from the investigated domain and collecting multi-frequency and multi-monostatic data. The imaging problem is formulated in a constant depth plane by exploiting the Born approximation. Hence, a linear inverse scattering problem is faced by considering both the Adjoint and the Truncated Singular Value Decomposition reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the previous section, we concluded that devising a data sampling strategy is equivalent to finding a proper quadrature role to approximate the integral representation of ps f adj . In the event that the measurement domain is in the far field [47], or even when the Fresnel paraxial approximation works [28], the matter is relatively straightforward, since the scattering operator can be given in terms of a Fourier transform and the data can be sampled according to the Nyquist sampling rate. When far-field conditions or the Fresnel approximations do not hold, the spatial frequency band of the scattered field can be estimated by invoking stationary phase arguments and the Nyquist step set accordingly (as shown in [34,35,48]).…”
Section: The Warping Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous section, we concluded that devising a data sampling strategy is equivalent to finding a proper quadrature role to approximate the integral representation of ps f adj . In the event that the measurement domain is in the far field [47], or even when the Fresnel paraxial approximation works [28], the matter is relatively straightforward, since the scattering operator can be given in terms of a Fourier transform and the data can be sampled according to the Nyquist sampling rate. When far-field conditions or the Fresnel approximations do not hold, the spatial frequency band of the scattered field can be estimated by invoking stationary phase arguments and the Nyquist step set accordingly (as shown in [34,35,48]).…”
Section: The Warping Samplingmentioning
confidence: 99%
“…However, recent developments have shown many advantages in using non-contact GPRs-for example, with GPRs mounted on a flaying platform [26,27]. In these cases, the spatial data sampling determines the trajectory-for example, in terms of the number of times that the radar needs to pass over the investigated area [28] or the number of flaying platforms that must populate the fleet in the case of a multistatic configuration [25].…”
Section: Introductionmentioning
confidence: 99%